2015
DOI: 10.1128/mcb.01181-14
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoporin 62-Like Protein Activates Canonical Wnt Signaling through Facilitating the Nuclear Import of β-Catenin in Zebrafish

Abstract: c Nucleoporin p62 (Nup62) localizes in the central channel of nuclear pore complexes (NPCs) and regulates nuclear pore permeability and nucleocytoplasmic transport. However, the developmental roles of Nup62 in vertebrates remain largely unclear. Zebrafish Nup62-like protein (Nup62l) is a homolog of mammalian Nup62. The nup62l gene is maternally expressed, but its transcripts are ubiquitously distributed during early embryogenesis and enriched in the head, pharynx, and intestine of developing embryos. Activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 108 publications
3
35
0
Order By: Relevance
“…The malignant activation of the Wnt signaling pathway leads to the onset of multiple types of cancers20. Meanwhile, β-catenin is a key activator of the canonical Wnt signaling pathway21. The abnormal accumulation and nuclear translocation of β-catenin play an important role in all of the β-catenin mutations22.…”
Section: Discussionmentioning
confidence: 99%
“…The malignant activation of the Wnt signaling pathway leads to the onset of multiple types of cancers20. Meanwhile, β-catenin is a key activator of the canonical Wnt signaling pathway21. The abnormal accumulation and nuclear translocation of β-catenin play an important role in all of the β-catenin mutations22.…”
Section: Discussionmentioning
confidence: 99%
“…We further created pCMV-Tag2C-RING1A-C398A using a PCR-based method 11, 12 . Briefly, PCR reaction was performed using primer pair: C398A Mutation-Forward (5′-CGGCCACTGGAGCTGGCCTATGCTCCCACCAAGGATCCAAAG-3′) and C398A Mutation-Reverse (5′-TTGGTGGGAGCATAGGCCAGCTCCAGTGGCCGGGACAC-3′).…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, nuclear levels of activated Dorsal were reduced in response to infection when Nup88 is deleted (Uv et al, 2000). Nup88 (Genenncher et al, 2016) along with other nucleoporins like Nup62 (Yang et al, 2015), Nup153 and Nup214 (Xu et al, 2002) are shown to be critical in developmental pathways, but detailed analyses emphasizing on their involvement in selective nuclear translocation of activated signals. In contrast, we report sustained activation of NF-B signaling and its accumulation inside the nucleus only upon dElys depletion but not with other nucleoporins involved nuclear pore complex assembly.…”
Section: Discussionmentioning
confidence: 99%